Pemberdayaan Masyarakat Desa Tanjung Qencono melalui Pelatihan Kewirausahaan Berbasis Produk Buket Kreatif - Nina Ikhwati Wahidah; Pixyoriza Pixyoriza; Iskandar Iskandar; Cholida Nur Fajri; Aulfa Reyza Ayuni Prestika (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This Community Service activity aims to empower the community of Tanjung Qencono Village through entrepreneurship training based on creative bouquet products. The background to this activity is the low level of entrepreneurial skills, human resource utilization, and management and marketing capabilities of village businesses. The implementation method includes preparation, entrepreneurship training and creative bouquet production, business management and digital marketing mentoring, business group formation, and evaluation. The training was conducted in a participatory manner with hands-on practice so that participants are able to produce marketable and competitive creative bouquet products. The results of the activity demonstrated an increase in participants' technical skills in creative bouquet production, simple financial record keeping, and the use of social media as a marketing tool. Furthermore, several creative business groups were formed that actively collaborate and demonstrate a high motivation for entrepreneurship. This activity has had a positive impact on increasing the community's economic independence and opening up sustainable creative business opportunities based on local potential.